How Can Gamification Help Language Learners? Insight From EFL Students And Teachers - Afifah, Afifah; Priyana, Joko (International Journal of Educational Research & Social Sciences, 2024)
Gamification, integrating game elements in non-game environments, has garnered significant interest as an educational strategy. However, there is a need for more research focusing on its efficacy in learning English as a Foreign Language (EFL). This study aims to address this gap by exploring EFL students' learning experiences with gamification and synthesizing the factors that enhance language learning. In this study, four vocational school students and an EFL teacher participated in a classroom where gamification techniques were implemented for four consecutive weeks. To gather data, individual semi-structured interviews were conducted with the participants to gain insights into their perspectives. The data were then analyzed using thematic analysis. The findings of this study highlight the significant contributions of gamification in EFL learning by leading to better student engagement (behavioral, emotional, and cognitive), and providing immediate feedback and task level. Keywords: gamification, language learning, EFL, educational strategy,